2022
DOI: 10.3389/fenvs.2022.1008441
|View full text |Cite
|
Sign up to set email alerts
|

Divergent trends of ecosystem status and services in the Hexi Corridor

Abstract: In terms of ecosystem structure, quality, and service, we have constructed a total of 18 characteristic evaluation indicators that could reflect the “state change interaction” of the ecosystem and analyzed the Spatio-temporal change of the ecosystem in Hexi Corridor from 2000 to 2020. The results show that: 1. The improvement of ecosystem and service is more obvious in the areas with a better ecological background in the East. The supply and regulation services of the ecosystem are synergetic. 2. In the past 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…We found that ESs are mainly low-low spatial matching areas, and are concentrated in the Desert Areas. Therefore, we should protect the ecological environment in the southern Qilian Mountains, strengthen regional ecological management, and maintain the integrity of the ecosystem 40 , 41 . For the core area of Qilian Mountains, we should strengthen the protection of the Qilian Mountains glacier and water conservancy ecological function area in the future.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…We found that ESs are mainly low-low spatial matching areas, and are concentrated in the Desert Areas. Therefore, we should protect the ecological environment in the southern Qilian Mountains, strengthen regional ecological management, and maintain the integrity of the ecosystem 40 , 41 . For the core area of Qilian Mountains, we should strengthen the protection of the Qilian Mountains glacier and water conservancy ecological function area in the future.…”
Section: Discussion and Analysismentioning
confidence: 99%